Maternal vitamin D and neonatal anthropometrics and markers of neonatal glycaemia: Belfast Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study. Issue 1 (25th June 2018) - Casey, Claire; McGinty, Ann; Holmes, Valerie A.; Patterson, Chris C.; Young, Ian S.; McCance, David R.
Abstract: Vitamin D deficiency is a common occurrence globally, and particularly so in pregnancy. There is conflicting evidence regarding the role of vitamin D during pregnancy in non-skeletal health outcomes for both the mother and the neonate. The aim of this study was to investigate the associations of maternal total 25-hydroxy vitamin D (25OHD) with neonatal anthropometrics and markers of neonatal glycaemia in the Belfast centre of the Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study. Serological samples ( n 1585) were obtained from pregnant women in the Royal Jubilee Maternity Hospital, Belfast, Northern Ireland, between 24 and 32 weeks' gestation as part of the HAPO study. 25OHD concentrations were measured by liquid chromatography tandem-MS. Cord blood and neonatal anthropometric measurements were obtained within 72 h of birth. Statistical analysis was performed. After adjustment for confounders, birth weight standard deviation scores (SDS) and birth length SDS were significantly associated with maternal total 25OHD. A doubling of maternal 25OHD at 28 weeks' gestation was associated with mean birth weight SDS and mean birth length SDS higher by 0·05 and 0·07, respectively (both, P =0·03). There were no significant associations with maternal 25OHD and other measures of neonatal anthropometrics or markers of neonatal glycaemia. In conclusion, maternal total 25OHD during pregnancy was independently associated with several neonatal anthropometric measurements; however, this association was relatively weak.